-7(1+3n)=-112

Simple and best practice solution for -7(1+3n)=-112 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(1+3n)=-112 equation:


Simplifying
-7(1 + 3n) = -112
(1 * -7 + 3n * -7) = -112
(-7 + -21n) = -112

Solving
-7 + -21n = -112

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -21n = -112 + 7

Combine like terms: -7 + 7 = 0
0 + -21n = -112 + 7
-21n = -112 + 7

Combine like terms: -112 + 7 = -105
-21n = -105

Divide each side by '-21'.
n = 5

Simplifying
n = 5

See similar equations:

| 7x-2=110000000000 | | -2v+4v=12+5v | | 7x-2=11000000 | | 6n^2-7=0 | | 2n+3.4=5.8 | | 5x-8+3y=180 | | 25x-7-16x+4=22x-6-13x+11 | | 16-6=-n | | 3(5x-12)=6g | | 3(1x+4)+5x=-20 | | 4(1+6x)=-140 | | 5x-8+132=180 | | 3x^3+15x^2+9x-5=0 | | 19284734x-91203=92 | | y^2+y=8 | | Y=x^3-12x+17 | | -6-3n=-7n-6+4n | | -6(x-4)=-4(x-8) | | x+(x+1)+(x+2)=-75 | | 5(-2m)+4=89 | | 2b+5p=5.2 | | 3(x-4)+68=-4 | | -r+1=-7+4r-r | | 2(3x-13)=-20 | | 3(c+2+1)=9c+3 | | 86=5x-14 | | y+6-4y-3=-30 | | 1-n=13-4n | | -5(x+3)(x+8)= | | 9x^2-18w+24=0 | | 30c=18360 | | 2(1-16a)=-2a-6(a-7) |

Equations solver categories